Which Fault Threatens Me Most? Bridging the Gap Between Geologic Data-Providers and Seismic Risk Practitioners - Scotti, Oona; Visini, Francesco; Faure Walker, Joanna; Peruzza, Laura; Pace, Bruno; Benedetti, Lucilla; Boncio, Paolo; Roberts, Gerald (Frontiers in Earth Science, 2021)
The aim of the Fault2SHA European Seismological Commission Working Group Central Apennines laboratory is to enhance the use of geological data in fault-based seismic hazard and risk assessment and to promote synergies between data providers (earthquake geologists), end-users and decision-makers. Here we use the Fault2SHA Central Apennines Database where geologic data are provided in the form of characterized fault traces, grouped into faults and master faults, with individual slip rate estimates. The proposed methodology first derives slip rate profiles for each master fault. Master faults are then divided into distinct sections of length comparable to the seismogenic depth. The use of sections allows consideration of variable slip rates along master faults and further allows building multi-fault rupture scenarios in hazard and risk computations. The methodology further allows exploration of epistemic uncertainties documented in the database (e.g. master fault definition, slip rates) as well as additional parameters required to characterize the seismogenic potential of fault sources (e.g. 3D fault geometries). Here we consider only one branch of the uncertainties affecting each step of the computation procedure, to illustrate the power of the methodology. The resulting hazard and typological risk maps allow both data providers and end-users to visualize the faults that threaten specific localities the most, to appreciate the density of observations used for the computation of slip rate profiles, and the degree of confidence on the fault parameters documented in the database (activity and location certainty). Finally, closing the loop, the methodology highlights priorities for future geological investigations in terms of where improvements in the density of data within the database would lead to the greatest decreases in epistemic uncertainties in the hazard and risk calculations. Key to this new generation of fault-based seismic hazard and risk methodology are the user-friendly open source codes provided with this publication, documenting, step-by-step, the link between the geological database and the relative contribution of each section to seismic hazard and risk at specific localities.